The Subject of Culture Within the Objective Scope of the Philosophy of Education - Svitlana Cherepanova (International Society of Philosophy and Cosmology, 2017)
In the article it is pointed out that European and worldwide integration processes, the informatization and the competitive character of all the spheres of social life require the overcoming of the tendency of "catching up" that is characteristic of Ukraine - in favour of leaving behind the transformation of the educational sphere, especially the pedagogical one. The attitude of a human being to the world contains theoretical (knowledge and ideas) and practical aspects. Created in the process of social development new establishments, things, technologies have a human content; implement human subjectivity - knowledge, intellect, feelings, thinking, volition, convictions, objectives etc. Under discordant challenges of globalization, the philosophy of education can provide an adequate answer, approaches and objectives. The philosophy of education functions as a combination of world view theories (ideas), scientific, cultural, value, moral and ethical principles that predetermine not only the content of education but also a certain type of personality... This takes into account the peculiarities of technogenic (western) and traditional (eastern) cultures, that is the type of personality: individualistic (the West), collectivistic (the East). The methodological prospects are determined by the correlation of humanitarian, dialogical, synergetic paradigms, the philosophic anthropology and ontology with the accent on culture creation as overcoming the boundaries of the possible (cognition, activity) creation of the being by means of culture. The humanitarian and culture creating strategies of the philosophy of education are grounded as conceptually reasonable: integrity and interaction of basic being and value concepts (man-science-culture-art-the style of thinking) and objectives - the formation of a personality as a subject of culture. The formation of the subject of culture takes place in a certain social community, among moral rules, customs and traditions. Because of essential differences between the East and the West (philosophical, political, economical, sociocultural) it is culture that helps to preserve and develop national educational systems. Creative potential of subject of culture in the subject field of philosophy of education is considered. But a classic Lviv Ivan Franko national University and "New School" (a project of Ministry of Education and Science of Ukraine) show substantial contradictions in relation to the preparation of a teacher to education and studies of creative personality. Accordingly, the preparation of a teacher needs the methodological updating, taking into account the distribution of digital technologies. The self-organization of the subject of culture is revealed in the sphere of synergetic. That is the open humanitarian scope, transdisciplinary achievements of science, education, culture, art, new tendencies of interaction between nature-man-culture-society-the Universe: dialogical, communicative, intersubjective, existential, culture creativel, rational. The ontological openness of the philosophy of education as a systemic phenomenon personifies the being of a man in the mental signs, and at the same time as a subject of culture, a subject of history, a subject of nation, a subject of the world